THE EFFECT OF AUDIO-LINGUAL METHOD IN TEACHING SPEAKING - Mul Muliadi; Muhammad Padli; Anggun Pratama; Harwadi Harwadi (LPPM Institut Pendidikan Nusantara Global, 2020)
This study aimed at finding out the effect of audio-lingual method in teaching speaking of MTs MTs Al-Amin NW Bagek Empat. The method used to analyze the obtaining data was an experimental research. The sample of this study was divided into two groups those were experimental group and control group. Each group consist of 40 students. The result of this study was significant by using of audio-lingual method in teaching speaking. It was proved by the result of t-test was 6.665 and t-table was 1.617 (6.665>1.617) mean scores of experimental groups were 1.8, while for control group were 0.65. Based on the hypothesis that was proposed the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.